CERITA RAKYAT DARI BALI: BEBERAPA KEJANGGALAN LINGUISTIS - I Dewa Putu Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2004)
This paper aims to show the role of linguistic competence in the Indonesian folk tale writing activities, especially the writer for whom Balinese is not his or her native language. Some linguistic mistakes found in the story book entitled